2020
DOI: 10.1038/s41598-020-71909-8
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of heart rhythm complexity in heart failure detection and diagnosis

Abstract: Heart failure (HF) is a major cardiovascular disease worldwide, and the early detection and diagnosis remain challenges. Recently, heart rhythm complexity analysis, derived from non-linear heart rate variability (HRV) analysis, has been proposed as a non-invasive method to detect diseases and predict outcomes. In this study, we aimed to investigate the diagnostic value of heart rhythm complexity in HF patients. We prospectively analyzed 55 patients with symptomatic HF with impaired left ventricular ejection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Findings from previous studies have indicated a strong negative correlation of the short-term scaling exponent of RR interval series with the level of sympathetic activity, i.e., with the plasma levels of circulating catecholamines [ 42 ]. Therefore, it is expected that in heart failure, accompanied by strong sympathetic activation, a decrease in the value of this exponent is recorded [ 43 ]. Moreover, it has been shown that lower α 1 (RR) is associated with increased mortality and hospitalization rate in patients with heart failure and that this exponent is independent predictor of heart failure [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from previous studies have indicated a strong negative correlation of the short-term scaling exponent of RR interval series with the level of sympathetic activity, i.e., with the plasma levels of circulating catecholamines [ 42 ]. Therefore, it is expected that in heart failure, accompanied by strong sympathetic activation, a decrease in the value of this exponent is recorded [ 43 ]. Moreover, it has been shown that lower α 1 (RR) is associated with increased mortality and hospitalization rate in patients with heart failure and that this exponent is independent predictor of heart failure [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is expected that in heart failure, accompanied by strong sympathetic activation, a decrease in the value of this exponent is recorded [ 43 ]. Moreover, it has been shown that lower α 1 (RR) is associated with increased mortality and hospitalization rate in patients with heart failure and that this exponent is independent predictor of heart failure [ 43 , 44 ]. We found that in CRT responders, nine months after device implantation, α 1 (RR) increases slightly but reaches values that are statistically significantly higher than in non-responders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising nonlinear tools have been introduced to describe the complexity of HRV, which presents the advantage of not being affected by nonstationary effects than typical linear HRV indexes 17 . The nonlinear methods have shown great promise in the detection and diagnosis of heart failure 18 . However, in BCS, the nonlinear properties of cardiac dynamics related to changes in the autonomic nervous system (ANS) and complexity have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Both methodologies are especially useful given that minimize the effects of non-stationarities 22,23 . The nonlinear methods have shown great promise in the detection and diagnosis of heart failure 24 and the evaluation of physical condition and wellbeing during physical activity tests 25 . However, in BCS, the nonlinear properties of cardiac dynamics related to changes in the autonomic nervous system (ANS) and complexity have not been fully elucidated.…”
mentioning
confidence: 99%